LITE SABR M1: Planning design and dosimetric endpoints for a phase I trial of lattice SBRT. (February 2022) - Kavanaugh, James A.; Spraker, Matthew B.; Duriseti, Sai; Basarabescu, Franco; Price, Alex; Goddu, Murty; Knutson, Nels; Prusator, Michael; Robinson, Clifford; Mazur, Thomas
Highlights: Refined treatment planning techniques improve Lattice SBRT plan quality. Patient treatment times for Lattice SBRT are scheduled in standard time slots. All treatment plan quality objectives are achievable. Existing plan evaluation metrics are insensitive to dose gradient variations. Updated planning metrics quantify deviations of dose gradients within targets. Abstract: Purpose: Lattice stereotactic body radiation therapy (SBRT) is a form of spatially fractionated radiation therapy (SFRT) using SBRT methods. This study reports clinical dosimetric endpoints achieved for Lattice SBRT plans delivering 20 Gy in 5 fractions to the periphery of a tumor with a simultaneous integrated boost (SIB) of 66.7 Gy, as part of a prospective Phase I clinical trial (NCT04133415). Additionally, it updates previously reported planning and delivery techniques based on extended experience with a broader patient population. Methods: Patients were enrolled on a single-arm phase I trial conducted between November 2019 and August 2020. Eligibility was restricted to tumors >4.5 cm in the largest dimension. Characteristic SFRT dose gradients were achieved using a lattice of 1.5 cm diameter spheres spaced within the GTV in a regular pattern, with peak-to-valley dose varying from 66.7 Gy to 20 Gy within 1.5 cm. Organ-at-risk (OAR) sparing followed AAPM TG101 recommendations for 5-fraction SBRT. Results: Twenty patients (22 plans) were enrolled on study, with one additional plan treated off study. All OAR and target coverage planning objectives were achieved, with the exception of a single small bronchus. Conformity of the 20 Gy isodose line significantly improved over the course of the study. The majority (85.2%) of treatment fractions were delivered in a 30 minutes timeslot, with 4 (3.5%) exceeding a total treatment time of 40 minutes. Conclusion: Lattice SBRT planning techniques produce consistent and efficient treatment plans. Refined techniques described here further improve the quality of the planning technique.